2011
DOI: 10.1182/blood-2011-04-349985
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the second zinc finger of human EKLF reduce promoter affinity but give rise to benign and disease phenotypes

Abstract: Mutations in the human erythroid Krü ppellike factor (EKLF) can lead to either anemia or the benign InLu phenotype. To elucidate the relationship between these mutations and the differing phenotypes, we prepared recombinant forms of wildtype and 5 mutant EKLF proteins and quantitated their binding affinity to a range of EKLF-regulated genes. Missense mutants (R328H, R328L, and R331G) from persons with InLu phenotype did not bind DNA. Hence, as with the heterozygous loss of function nonsense (L127X, S270X, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 43 publications
4
48
0
Order By: Relevance
“…Surprisingly, compound heterozygotes of the KLF1 mutations c.809C4A (p. (Ser270Ter)) and c.994A4C (p.(Lys332Gln)), both of which affect the ZF domain, did not produce severe anemia or a β-thalassemia phenotype, suggesting that the c.994A4C (p.(Lys332Gln)) mutation has little impact on the transactivation capacity of KLF1. 13,17 Furthermore, the HS2 − γ prom/ Renilla − β prom/Firefly reporter assay demonstrated that the compound c.994A4C (p.(Lys332Gln)) mutations in the Sardinian family had less effect than the mutations described in the present study. (Supplementary Figure S4).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Surprisingly, compound heterozygotes of the KLF1 mutations c.809C4A (p. (Ser270Ter)) and c.994A4C (p.(Lys332Gln)), both of which affect the ZF domain, did not produce severe anemia or a β-thalassemia phenotype, suggesting that the c.994A4C (p.(Lys332Gln)) mutation has little impact on the transactivation capacity of KLF1. 13,17 Furthermore, the HS2 − γ prom/ Renilla − β prom/Firefly reporter assay demonstrated that the compound c.994A4C (p.(Lys332Gln)) mutations in the Sardinian family had less effect than the mutations described in the present study. (Supplementary Figure S4).…”
Section: Discussionmentioning
confidence: 51%
“…14 Studies suggest that the amount and type of mutant KLF1 protein produced are responsible for different RBC phenotypes. [15][16][17][18] Further research is required to determine the relationship between the various KLF1 mutations and the severity of clinical phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…In the present case, the most direct connection is with CDA type IV (Iolascon et al, 2012), which is caused by a mutation in human KLF1 at the same amino acid (Arnaud et al, 2010;Jaffray et al, 2013;Singleton et al, 2011). The change is non-conservative (E to K), so although not all characteristics of the Nan mouse may apply, individuals with CDA exhibit altered globin switching and membrane deficits that are highly reminiscent of the present model (discussed by Siatecka et al, 2010b).…”
Section: Discussionmentioning
confidence: 84%
“…However, some mutations lead to anemias (Arnaud et al, 2010;Huang et al, 2015;Jaffray et al, 2013;Singleton et al, 2011;Viprakasit et al, 2014; reviewed by Perkins et al, 2016). The human KLF1 mutation (E325K) in congenital dyserythropoietic anemia (CDA) (Arnaud et al, 2010;Jaffray et al, 2013;Singleton et al, 2011) is at the same amino acid as that seen in the mouse Nan mutant (Heruth et al, 2010;Siatecka et al, 2010b), albeit a different substitution. Nan is inherited in a semi-dominant fashion: homozygotes die in utero at E10-11, while heterozygous Nan/+ mice exhibit lifelong severe anemia that is characterized by reticulocytosis, splenomegaly, altered globin expression and cell membrane defects (Lyon, 1983;Siatecka et al, 2010b;White et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This variant is altered within the second zinc finger (E325K), changing its cognate binding specificity and probably converting it to an interfering protein (Singleton et al, 2011). In this context, it is interesting to compare these observations to that of the Nan mouse, which harbors a mutation at the same site but with a different substitution (E339D) (Heruth et al, 2010;Siatecka et al, 2010).…”
Section: Discussion Cellular and Mechanistic Aspects Of Erythroid/macmentioning
confidence: 99%